2019
DOI: 10.5312/wjo.v10.i12.454
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with trigger digit following carpal tunnel release

Abstract: BACKGROUNDTrigger digit is a common disorder of the hand associated with carpal tunnel syndrome. Carpal tunnel release (CTR) surgery may be a risk factor for trigger digit development; however, the association between surgical approach to CTR and postoperative trigger digit is equivocal.AIMTo investigate patient risk factors for trigger digit development following either open carpal tunnel release (OCTR) or endoscopic carpal tunnel release (ECTR).METHODSThis retrospective chart analysis evaluated 967 CTR proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Endoscopic carpal tunnel release was an independent risk factor for the trigger finger. This contrasts with Nosewicz et al [12] and Harada et al [18], who found endoscopic carpal tunnel release was not a risk factor. Shafee-Khanghah et al [14] retrospectively reviewed 57 consecutive patients who underwent trigger finger release surgery and found that 15 (26.3%) had undergone prior carpal tunnel release surgery approximately 6 months before trigger finger release.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Endoscopic carpal tunnel release was an independent risk factor for the trigger finger. This contrasts with Nosewicz et al [12] and Harada et al [18], who found endoscopic carpal tunnel release was not a risk factor. Shafee-Khanghah et al [14] retrospectively reviewed 57 consecutive patients who underwent trigger finger release surgery and found that 15 (26.3%) had undergone prior carpal tunnel release surgery approximately 6 months before trigger finger release.…”
Section: Discussionmentioning
confidence: 62%
“…Nosewicz et al [12] performed a retrospective chart analysis of 967 carpal tunnel release procedures (open or endoscopic) in 694 patients. 64 trigger digits were seen postoperatively in 47 hands (4.9%).…”
Section: Discussionmentioning
confidence: 99%
“…For the incidence of post-CTR TF, a sample size of 9207 was included in the final analysis. The data of post-CTR TF were provided as number of people in five studies 16 18 , 21 , 22 and number of hands in five studies 15 , 19 , 20 , 23 , 24 . Four studies 17 , 18 , 23 , 24 were conducted in the United States, four in Asia (two in Japan 19 , 20 , one in Korea 21 , one in Taiwan 22 ), and two in Europe (one in Turkey 15 and one in Spain 16 ).…”
Section: Resultsmentioning
confidence: 99%
“…The data of post-CTR TF were provided as number of people in five studies 16 18 , 21 , 22 and number of hands in five studies 15 , 19 , 20 , 23 , 24 . Four studies 17 , 18 , 23 , 24 were conducted in the United States, four in Asia (two in Japan 19 , 20 , one in Korea 21 , one in Taiwan 22 ), and two in Europe (one in Turkey 15 and one in Spain 16 ). For subgroup analysis of patients with and without post-CTR TF, three studies 16 , 17 , 21 provide the number of men and women; three 16 , 17 , 21 provided data on the patients’ mean age; and three 17 , 18 , 21 reported the number of patients with DM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation